Prescription of Potentially Inappropriate Medication in Older Inpatients of an Internal Medicine Ward: Concordance and Overlap Among the EU(7)-PIM List and Beers and STOPP Criteria - Perpétuo, Carla; Plácido, Ana I.; Rodrigues, Daniela; Aperta, Jorge; Piñeiro-Lamas, Maria; Figueiras, Adolfo; Herdeiro, Maria Teresa; Roque, Fátima (Frontiers in Pharmacology, 2021)
Background: Age-related comorbidities prone older adults to polypharmacy and to an increased risk of Potentially Inappropriate Medication (PIM) use. This work aims to analyze the concordance and overlap among the EU(7)-PIM list, 2019 Beers and Screening Tool of Older Person´s Prescriptions (STOPP) version 2 criteria, and, also to analyze the prevalence of PIM. Methods: A retrospective cohort study was conducted on older inpatients of an internal medicine ward. Demographic, clinical, and pharmacological data were collected, during March 2019. After PIM identification by EU(7)-PIM list, Beers criteria, and STOPP v2 criteria, the concordance, and overlap between criteria were analyzed. A descriptive analysis was performed, and all the results with a p-value lower than 0.05 were considered statistically significant. Results: A total of 616 older patients were included in the study whose median age was 85 (Q1-Q3) (78-89) years. Most of the older patients were male (51.6%) and the median (Q1-Q3) number of days of hospitalization was 17 (13-22) days. According to the EU(7)-PIM list, the Beers criteria and STOPP criteria 79.7%, 92.0%, and 76.5% of older adults, respectively used at least one PIM. A poor concordance (<63.4%) among criteria was observed. An association between PIM and the number of prescribed medicines was found in all applied criteria. Moreover, an association between the number of PIM, and diagnoses of endocrine, nutritional and metabolic diseases and mental, behavioral, and neurodevelopmental disorder and circulatory system diseases and days of hospitalization were observed according to Beers criteria, and with diseases of the circulatory system and musculoskeletal system and connective tissue according to STOPP criteria. Conclusion: Although the poor concordance between EU(7)-PIM list, 2019 Beers, and STOPP v2 criteria, this work highlight the need for more studies in inpatients to develop strategies to facilitate the identification of PIM to decrease the high prevalence of PIM in hospitalized patients. The poor concordance among criteria also highlights the need to develop new tools adapting the existing criteria to medical ward inpatients.